2020
DOI: 10.1123/jpah.2019-0476
|View full text |Cite
|
Sign up to set email alerts
|

Hydration Does Not Change Postexercise Hypotension and Its Mechanisms

Abstract: Background: Drinking water is recommended before and after exercise to avoid dehydration. However, water ingestion may mitigate or prevent postexercise hypotension. This study investigated the effects of intentional hydration on postaerobic exercise hemodynamics and autonomic modulation. Methods: A total of 18 young men randomly underwent 4 experimental sessions as follows: (1) control with intentional hydration (1 L of water in the previous night, 500 mL 60 min before the intervention, and 1 mL for each 1 g o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Moreover, the marginal consistencies of PEH hemodynamic determinant were mainly observed for SV, CO and SVR that can be influenced by pre-exercise plasma volume and hydration status that were not checked in the current study. Although this lack of control could initially be interpreted as a relevant limitation, it is important to highlight that the current study emulates most of the PEH studies' designs that do not control hydration status, and that a recent study using a similar protocol reported no difference in plasma volume and hydration status before different exercise and control sessions (35). Finally, as a first study on PEH consistency, this study involved a comprehensive sample composed by individuals of both sexes, at different age groups, and with a large variation in BMI and BP status.…”
Section: Discussionmentioning
confidence: 90%
“…Moreover, the marginal consistencies of PEH hemodynamic determinant were mainly observed for SV, CO and SVR that can be influenced by pre-exercise plasma volume and hydration status that were not checked in the current study. Although this lack of control could initially be interpreted as a relevant limitation, it is important to highlight that the current study emulates most of the PEH studies' designs that do not control hydration status, and that a recent study using a similar protocol reported no difference in plasma volume and hydration status before different exercise and control sessions (35). Finally, as a first study on PEH consistency, this study involved a comprehensive sample composed by individuals of both sexes, at different age groups, and with a large variation in BMI and BP status.…”
Section: Discussionmentioning
confidence: 90%